On route to the Olympic podium: A comparative New Zealand Youth Rugby Sevens match analysis - Wintershoven, K.; Beaven, C. M.; Gill, N. D.; McMaster, D. T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: 9.6 million people play rugby in 124 countries and 40 teams will compete in the 2022 Rugby World Cup Sevens. Rugby Sevens (7s) has gained in popularity since its introduction to the 2016 Olympics and the 2018 Youth Olympics saw 11 countries from 6 regional associations compete at 7s. Rugby 7s school youth participation has grown by 185% between 2012 and 2020 in New Zealand. While microsensor technology has been applied to field-based sports, little is known about the physical demands of Youth Rugby 7s.